How do Sustainable Business Models Create Value at the Bottom of the Pyramid - Kingscote, Daniel James (2015)
Abstract The purposes of this dissertation research was to understand the role, method and results of the operation of sustainable business models at the Bottom of the Pyramid. In order to do this one sustainable business model was chosen in rural Malawi to examine in order for this case research to be conducted. 15 individuals that had close connections with the business, ranging from the Director to the consumers that it served in order to evaluate how this sustainable business model generated different kinds of value for different individuals at the Bottom of the Pyramid. Two key themes emerged from this research – that of how the value was created and delivered in order to facilitate the benefits for the Bottom of the Pyramid consumers, and the different types of value that were captured by these individuals. Based on these findings this study poses that sustainable business models can be the solutions to some of the world’s complex and difficult problems. Analysing the importance of both social and environmental value creation to solving these issues, the research discusses how members of the Bottom of the Pyramid themselves have experienced the role of the sustainable business models in both its limitations and benefits for them. Citing the shortfallings of both charity and aid, and conventional business models in solving these issues this study recommends further study and analysis of other sustainable business models in order to confirm these hypothesis in a wider context.